Exploring pathways towards an integrated development role: The University of Fort Hare - Grobbelaar, S; de Wet, G (South African Journal of Higher Education, 2016)
The conditions under which universities are attempting to coherently accomplish their three missions of teaching and learning, research and community engagement have a significant impact on the institutional form, structure and character of universities. The concept of the developmental state, the role and place for the Higher Education sector in the developmental state and its role in supporting political, social and economic transformation is explored. In this paper we attempt to further develop a conceptual framework for the development(al) university considering the context, drivers of focus, and changes in control, governance and university functions to the end of defining a potential development pathway. The research problem addressed in this paper is therefore not an attempt to extend the “research university” or “entrepreneurial university” concept but to rather discuss the pathways through which a university may strengthen its development role as “instrument” or “engine”. The empirical analysis presented in the article is a case study of an agricultural development project at the University of Fort Hare in South Africa. We analyse the case study against the development pathway framework and explore its utility to facilitate understanding and learning within the University towards reaching development and transformation objectives. We propose that such a framework could support understanding of the impact universities have on the economy and society beyond typical mechanistic measures.